Exploring the correlation between new function attributes mined from different product domains and market sales. Issue 2 (3rd April 2018) - Kang, Sung Woo; Tucker, Conrad S.
ABSTRACT: In order to satisfy various market needs and remain competitive in the marketplace, high-technology industries create cross-domain products that are differentiated from current product designs by integrating new function attributes from multiple product domains. However, given the vast number of candidate function attributes to select from, there is a fundamental challenge when searching for the appropriate function attributes to include in next-generation products. This work quantifies the semantic similarities between descriptive design requirements and function attributes in order to identify new function attributes that have the highest similarity to each requirement. This work hypothesizes that there is a correlation between these new function attributes and increased product sales. The case study presented in this work tests this hypothesis in the mechanical transmission systems domain. This work analyzes the impacts of products that contain different function attributes on actual product sales in the market. Transmission system function attributes and product sales data, including new electronic gear shifting systems from Shimano's bicycle division, are introduced in the case study. This case study reveals that the function attributes predicted by the method increase the market sales of next-generation products.